Activity-Based Costing and Firm Performance: Evidence from Innovative Business Organizations - Kerem (Journal of Business Innovation and Accounting Research, 2026)
This study investigates the relationship between Activity-Based Costing (ABC) implementation and firm performance within innovative business organizations operating in Turkey. Drawing upon the resource-based view and knowledge-based theory, this research examines how ABC adoption influences financial and non-financial performance outcomes in Turkish firms characterized by innovation-oriented strategies. The methodology employs a quantitative research design utilizing structural equation modeling (SEM) to analyze data collected from manufacturing and technology-intensive firms across Turkey's major industrial regions. The findings reveal that ABC implementation demonstrates a significant positive relationship with firm performance, particularly when mediated by innovation capacity and strategic cost management practices. Furthermore, the results indicate that firms adopting ABC systems exhibit enhanced decision-making capabilities, improved resource allocation efficiency, and superior competitive positioning in dynamic market environments. The study contributes to the existing literature by providing empirical evidence from an emerging market context, specifically addressing the intersection of management accounting practices and innovation performance in Turkish business organizations. The implications suggest that innovative firms in Turkey can leverage ABC systems to achieve sustainable competitive advantages through more accurate cost information and enhanced strategic planning capabilities.